Male breast hypertrophy - a review of modern methods of treatment - Wojcik, Rafal; Adanczyk, Katarzyna; Adamczyk, Dorota; Kozak, Krzysztof; Czerwonka, Maciej; Dziedzic, Mateusz; Madej–Czerwonka, Barbara (Journal of Education, Health and Sport, 2018)
Gynecomastia is a benign enlargement of the mammary gland in males. Nowadays it is a common disorder of all ages, including newborns, adolescents and adults. It may be bilateral or unilateral enlargement of the breast. Gynecomastia may be a severe problem in adolescents resulting in development of psychological disorders. Evolution of surgical treatment options, depending on the degree of breast hypertrophy advancement, brought significant improvement in aesthetic effect and patient’s quality of life. This paper presents the development of pharmaceutical and surgical treatment technics. The manuscript proposes the optimal methods of clinical approach to the patients with an enlargement of the breast.